Analysis of a crankshaft fatigue failure. (September 2015) - Li, Wei; Yan, Qing; Xue, Jianhua
Highlights: Both experimental methods and theoretical calculation are used in this paper. High stress concentrations are the main reasons that lead to the fracture. Fatigue crack initiation region is around the fillet of the lubrication hole. The safety factors on two dangerous sections are compared in this paper. Abstract: The reason of the crankshaft fracture of the air compressor has been analyzed through the chemical composition, mechanical properties, macroscopic feature, microscopic structure and theoretical calculation methods. The analysis results show that the crankshaft which has obvious fatigue crack belongs to fatigue fracture. The fatigue crack initiated from the fillet region of the lubrication hole because of the high bending stress concentration which is caused by both the small fillet and the misalignment of main journals. The crankshaft fatigue fracture was only attributed to the initiation and propagation of the fatigue cracks on the lubrication hole under cyclic bending and torsion. The high bending loading bending level is the root cause of the failure.